TREATMENT OF DEMENTIA: RECOMMENDATIONS OF THE SCIENTIFIC DEPARTMENT OF COGNITIVE NEUROLOGY AND AGING OF THE BRAZILIAN ACADEMY OF NEUROLOGY - Caramelli, Paulo; Marinho, Valeska; Laks, Jerson; Coletta, Marcus Vinicius Della; Stella, Florindo [UNESP]; Camargos, Einstein Francisco; Smid, Jerusa; Barbosa, Breno José Alencar Pires; Schilling, Lucas Porcello; Balthazar, Marcio Luiz Figueredo; Frota, Norberto Anízio Ferreira; de Souza, Leonardo Cruz; et al. (FapUNIFESP (SciELO), 2022)
There is currently no cure for neurodegenerative or vascular dementias, but some pharmacological and non-pharmacological interventions may contribute to alleviate symptoms, to slow disease progression and improve quality of life. Current treatment approaches are based on etiology, symptoms’ profile and stage of dementia. In this manuscript we present recommendations about the pharmacological and non-pharmacological treatments of dementia due to Alzheimer’s disease, vascular cognitive impairment, frontotemporal dementia, Parkinson’s disease dementia and dementia with Lewy bodies.
Tratamento da demência: recomendações do Departamento Científico de Neurologia Cognitiva e do Envelhecimento da Academia Brasileira de Neurologia
Keywords: Behavior; Cognition; Dementia; Drug Therapy